Digitalisasi Kesehatan Prenatal sebagai Media Panduan dan Monitoring Kehamilan berbasis Mobile - Yodhi Anugrah Damar Saputra; Sri Wulandari (Universitas Hamzanwadi, 2023)
Maternal and Child Health book is an important tool as a reference in conducting pregnancy checks. However, in practice, this book is often overlooked or left behind when pregnant women consult with medical personnel, resulting in data discrepancies between MCH books and medical records. Purpose of the study Creating an online system in the form of an Android application that functions as a means of monitoring pregnancy by medical personnel in real-time, which also serves as a medium of guidance for pregnant women about the health of their pregnancy. This research was conducted at Puskesmas Rakit 1, Banjarnegara Regency, Central Java. This research method uses a waterfall model starting from problem analysis and data processing, designing GUI design systems and database designs, implementing programming languages, system integration and system testing using black boxes, to the system maintenance stage. This research produced an output in the form of an Android application to store pregnancy data that is synchronized in real-time and can be accessed online as a medium for guidance and monitoring of pregnancy health.